Modern classroom assessment - Frey, Bruce B. (Los Angeles SAGE, 2014)
Modern Classroom Assessment offers an applied, student-centered guide to the major research-based approaches to assessment in today's modern classroom. Rather than simply list basic assessment formats with a few examples, as many textbooks do, award-winning professor and scholar Bruce Frey's book fully explores all five key approaches for teacher-designed assessment--Traditional Paper-and-Pencil, Performance-Based Assessment, Formative Assessment, Universal Test Design, and Authentic Assessment --while making abstract concepts and guidelines clear with hundreds of real-world illustrations and examples of what actual teachers do. Offering a variety of engaging learning tools and realistic stories from the classroom, this text will give any reader a strong foundation for designing modern assessments in their own classrooms
Chapter 1. Modern classroom assessment -- Chapter 2. The language of classroom assessment -- Chapter 3. Basic assessment strategy: categories of learning, objectives, and backward design -- Chapter 4. Formative assessment -- Chapter 5. Summative assessment: traditional paper-and-pencil tests -- Chapter 6. Constructed-response items and scoring rubrics -- Chapter 7. Performance-based assessment -- Chapter 8. Authentic assessment -- Chapter 9. Universal test design -- Chapter 10. Test accommodations -- Chapter 11. Understanding scores from classroom assessments -- Chapter 12. Making the grade -- Chapter 13. Standardized tests
Title from title screen (viewed October 19, 2023)
Includes bibliographical references and index
Description based on MARC record for print version
Keywords: Educational tests and measurements -- United States; Educational tests and measurements -- Standards -- United States; Educational tests and measurements -- United States -- Design and construction